The attitude of the resuscitation team members and the patient’s companions toward the presence of the patient’s first-degree relatives during cardiopulmonary resuscitation in the emergency departments - M. N. Isfahani; F. B. Borojeni; F. Pakravan; B. Masoumi (Вестник анестезиологии и реаниматологии, 2023)
The presence of the patient’s family at their bedside during cardiopulmonary resuscitation (CPR) is one of the challenging issues that has been frequently taken into consideration. Considering the importance of this topic. The objective of the present study was conducted to determine the attitude of the CPR team members and the patient’s companions toward the presence of the patient’s first-degree relatives during CPR.Materials and methods. The descriptive-analytical cross-sectional study was conducted on 100 CPR team members of two University Hospitals and 120 near relatives of patients undergoing CPR in 2021. The data were collected by the researcher-made questionnaire and depression, anxiety, stress scale (DASS) during CPR. The collected data were analyzed by SPSS (version 22) statistical software.Results. From the perspective of both the CPR team members and the patient’s companions, the highest mean response was related to the fact that it would be better for the patient to agree on the presence or absence of their family before hospitalization and whether they have favorable conditions. The attitude toward the presence of the patient’s family during CPR was statistically significantly associated with the companions’ gender (p < 0.05) and with the experience of work and participation in CPR of the CPR team members (p < 0.05).Conclusion. Taking into account the different opinions of the CPR team members and the patient’s relatives about the presence of family during resuscitation, additional studies with a large sample size should be carried out.